1979
DOI: 10.2134/jeq1979.00472425000800010027x
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant Movement to Shallow Ground Water Tables from Anaerobic Swine Waste Lagoons

Abstract: The effect of three anaerobic swine waste lagoons on ground water quality was investigated in the Atlantic Coastal Plain region. The lagoons studied were located on high‐water‐table soils with different textures. Ground water was sampled from wells, with unperforated casings, located at depths to 6 m and distances to 30 m from the lagoons. These samples were taken monthly from September 1974 through January 1975, and bimonthly thereafter through November 1975. Ground water also was sampled in November 1975 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…As early as 1960s to 1970s, the NO 3 --N pollution problem in soil and groundwater caused by livestock manures appeared in many countries and regions with well-developed animal husbandry. Ciravolo et al (1979) reported that Cl -and NO 3 --N concentrations in the groundwater around a swine waste lagoon constructed on a sandy subsurface soil in the coastal plain region of Virginia exceeded the USEPA drinking water standard of 10 mg/L NO 3 -N. In south Netherlands, the livestock manures produced by animal husbandry exceeded the amount of normal agricultural use, resulting in the soil NO 3 --N pollution. Animal manures in Belgium are approximately 41.0 million tons every year, and 8.0 million tons in excess of the standard (Eli et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 1960s to 1970s, the NO 3 --N pollution problem in soil and groundwater caused by livestock manures appeared in many countries and regions with well-developed animal husbandry. Ciravolo et al (1979) reported that Cl -and NO 3 --N concentrations in the groundwater around a swine waste lagoon constructed on a sandy subsurface soil in the coastal plain region of Virginia exceeded the USEPA drinking water standard of 10 mg/L NO 3 -N. In south Netherlands, the livestock manures produced by animal husbandry exceeded the amount of normal agricultural use, resulting in the soil NO 3 --N pollution. Animal manures in Belgium are approximately 41.0 million tons every year, and 8.0 million tons in excess of the standard (Eli et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…NO 3 --N migrates much faster than ammonium under the same condition. A number of researches have been reported on nitrate level exceeding the safety limit in the neighboring areas of CAFOs (Ciravolo et al 1979;Eli et al 2004;Pierre et al 2005;Karr et al 2001;Evans et al 1984;Sloan et al 1999;David et al 2005;Donald et al 2001). Adsorption and desorption characteristics of ammonium played an important role in the regulation of the NH 4 ?…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of the environment can result from lagoon breaks and the subsequent release of millions of gallons of animal wastes directly into surface water at one time (1) or from seepage losses of lagoon wastewater into the surrounding soil and groundwater (11)(12)(13). In addition, land application of liquefied wastes may result in wastes leaching into groundwater or reaching streams as a result of overland flow (4,14).…”
Section: Swine Cafosmentioning
confidence: 99%
“…Studies in Iowa and North Carolina (11,14,(204)(205)(206) revealed groundwater contamination resulting from agricultural practices. Moderate to severe seepage losses from lagoons and groundwater pollution with nitrates and microbes, resulting in contamination in excess of drinking water standards, have been documented (11,14,(204)(205)(206) , NC) found that 22% of the tested wells in one county had nitrate levels which exceed the no-observed-adverse-effect level (79,2017).…”
Section: Environmental Dispersion Of Swine Cafo Hazardsmentioning
confidence: 99%
“…Swine waste storage systems have been shown to adversely impact ground water quality due to unintentional seepage through clay or earthen liners (Ciravolo et al, 1979 andChirnside, 1990). Ammonia, nitrate, dissolved solids, and chloride concentrations have been monitored as indicators of ground water quality near livestock production facilities.…”
Section: Physical and Chemical Characterization Of Stored Waste In Thmentioning
confidence: 99%